2018
DOI: 10.1371/journal.pone.0201517
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 level predicts response to ablation and outcomes in patients with persistent atrial fibrillation and systolic heart failure

Abstract: IntroductionMechanisms of maintenance of both atrial fibrillation and structural left ventricular disease are known to include fibrosis. Galectin-3, a biomarker of fibrosis, is elevated both in patients with heart failure and persistent atrial fibrillation. We sought to find whether galectin-3 has a prognostic value in patients with heart failure and a reduced left ventricular ejection fraction undergoing ablation of persistent atrial fibrillation.MethodsSerum concentrations of galectin-3 were determined in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
1
13
0
1
Order By: Relevance
“…Our results demonstrate that, despite the role of Gal-3 in AF pathogenesis, baseline circulating Gal-3 levels may predict the response to catheter ablation in AF patients. This is consistent with the results of a previous study that showed that baseline Gal-3 levels independently predict outcomes in patients with reduced left ventricular systolic function attributed to ablation of persistent AF [38]. Taken together, Gal-3 is likely involved in AF pathogenesis and progression, risk stratification for stroke incidence, and treatment response to catheter ablation.…”
Section: Discussionsupporting
confidence: 91%
“…Our results demonstrate that, despite the role of Gal-3 in AF pathogenesis, baseline circulating Gal-3 levels may predict the response to catheter ablation in AF patients. This is consistent with the results of a previous study that showed that baseline Gal-3 levels independently predict outcomes in patients with reduced left ventricular systolic function attributed to ablation of persistent AF [38]. Taken together, Gal-3 is likely involved in AF pathogenesis and progression, risk stratification for stroke incidence, and treatment response to catheter ablation.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Gal-3 has been indicated to be involved in the following broad pathological processes: Inflammation [9], fibrosis, cell-to-cell [10,11] or cell-to-matrix [12] contacts, cell proliferation [13,14], and protection from apoptosis [15,16]. Furthermore, many studies have revealed that Gal-3 expression is detected in many disease conditions, such as heart disease [17][18][19][20][21][22][23], kidney disease [24][25][26][27], diabetes mellitus [24,25,28], viral infection [29][30][31][32], autoimmune disease [33][34][35][36], neurodegenerative disorders [37][38][39][40][41][42], and tumor formation [43][44][45][46][47][48][49][50][51][52].…”
Section: Clinical Significance and Applications Of Galectine-3 (Gal-3)mentioning
confidence: 99%
“…Gal-3 is involved in the pathophysiology of HF [78] mainly because of its role in cardiac ventricular remodeling [71,77]. Normally, Gal-3 expression in the heart is low, whereas its synthesis and secretion increase in HF [63,79,80]. Gal-3 initially plays a protective role in the heart through its anti-apoptotic and anti-necrotic functions, while the prolonged expression of this protein leads to fibrosis and adverse remodeling of the damaged tissue [78].…”
Section: Gal-3 In Cardiac Fibrosis and Heart Failurementioning
confidence: 99%
“…Atrial fibrillation (AF) is the most frequent arrhythmia and it is associated with structural, electrical, genomic and hormonal atrial remodeling [79]. More recently, the concept of fibrotic atrial cardiomyopathy was introduced-defined as a progressive invasion of atrial myocardium by fibrosis, which favors initiation and maintenance of AF [83].…”
Section: Gal-3 and Other Cardiovscular Diseasesmentioning
confidence: 99%